1992
DOI: 10.1212/wnl.42.6.1239
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cisternal and lumbar CSF examination in leptomeningeal metastasis

Abstract: We compared cisternal and lumbar CSF examination in 14 patients suspected of having leptomeningeal metastasis from cancer. Malignant cells were present in 12 patients--in both cisternal and lumbar CSF in nine patients and only in cisternal CSF in three. Cisternal CSF cytologic examination should be considered in patients suspected of having leptomeningeal metastasis if lumbar CSF is nondiagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Of note, a series including lymphomatous and leukemic meningitis by Kaplan et al [3] observed the frequent dissociation between the CSF cell count and malignant cytology (29% of cytologically positive CSF had concurrent CSF counts Ͻ4/mm 3 ). Murray et al [22] and Rogers et al [22,23] showed that CSF levels of protein, glucose, and malignant cells vary at different levels of the neuraxis even if there is no obstruction of the CSF flow. This finding reflects the multifocal nature of neoplastic meningitis and explains why CSF obtained from a site distant to that of the pathologically involved meninges may yield negative cytology.…”
Section: Csf Examinationmentioning
confidence: 99%
“…Of note, a series including lymphomatous and leukemic meningitis by Kaplan et al [3] observed the frequent dissociation between the CSF cell count and malignant cytology (29% of cytologically positive CSF had concurrent CSF counts Ͻ4/mm 3 ). Murray et al [22] and Rogers et al [22,23] showed that CSF levels of protein, glucose, and malignant cells vary at different levels of the neuraxis even if there is no obstruction of the CSF flow. This finding reflects the multifocal nature of neoplastic meningitis and explains why CSF obtained from a site distant to that of the pathologically involved meninges may yield negative cytology.…”
Section: Csf Examinationmentioning
confidence: 99%
“…45 Several series have demonstrated that, in some cases, serial CSF sampling via lumbar puncture or sampling from alternate sites (eg, cisternal, ventricular) is required to detect malignant cells. 11,67,70,71 LDH concentrations are elevated in cases of stroke, bacterial meningitis, CSF pleocytosis, head injury, primary CNS tumors, and some metastases.…”
mentioning
confidence: 99%
“…Particular emphasis should be placed on examining CSF from sites of clinical or neuroradiographic disease, as these are more likely to be cytologically positive. Though not directly studied, the ndings in this study also suggest that the initial clinical or radiographic diagnosis of LM is more likely to be con rmed by CSF sampling directed at the site of clinical or neuroradiographic disease (Glantz et al, 1998;Rogers et al, 1992). These ndings have implications for both the clinical management and the design and interpretation of clinical trials involving patients with LM.…”
Section: Discussionmentioning
confidence: 59%